Nitazoxanide Inhibits Biofilm Production and Hemagglutination by Enteroaggregative Escherichia coli Strains by Blocking Assembly of AafA Fimbriae - Shamir, Eliah R. (American Society for Microbiology (ASM), 2010)
Enteroaggregative Escherichia coli (EAEC) strains have emerged as common causes of persistent diarrhea and malnutrition among children and HIV-infected persons. During infection, EAEC typically adheres to the intestinal mucosa via fimbrial adhesins, which results in a characteristic aggregative pattern. In the study described here we investigated whether the broad-spectrum antiparasitic and antidiarrheal drug nitazoxanide (NTZ) might be active against EAEC in vitro. While E. coli strains were resistant to NTZ in rich Luria-Bertani medium (MIC > 64 μg/ml), the drug was slightly inhibitory in a minimal medium supplemented with glucose (MinA-G medium; MIC, ∼32 μg/ml). NTZ also inhibited biofilm production by strain EAEC 042 in both Dulbecco's modified Eagle's medium and MinA-G medium with a 50% inhibitory concentration of ∼12 μg/ml. Immunofluorescence and immunoblot analyses with antibody against the major fimbrial subunit AafA of aggregative adherence fimbriae vaariant II (AAF/II) established that the numbers of AAF/II filaments on bacteria grown in the presence of NTZ were dramatically reduced. Comparative quantitative reverse transcription-PCR and reporter gene fusions (aafA::phoA) indicated that aafA expression was unaffected by NTZ, while aggR transcript levels and aggR::lacZ expression were increased ∼10- and 2.5-fold, respectively, compared with that for the untreated controls. More generally, NTZ inhibited hemagglutination (HA) of red blood cells by the non-biofilm-producing strain JM221 expressing either AAF/I or type I fimbriae. Our findings suggest that the inhibitory action of NTZ on biofilm formation and HA is likely due to inhibition of fimbrial assembly. Antimicrobial agents that inhibit the assembly or function of fimbrial filaments should be good candidates for the prevention of infection.